2021
DOI: 10.1101/2021.03.12.435175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconstructing human early embryogenesis in vitro with pluripotent stem cells

Abstract: Understanding human development is of fundamental biological and clinical importance. Yet despite its significance, insights into early developmental events in humans still remain largely unknown. While recent advances show that stem cells can mimic embryogenesis1-9 to unravel hidden developmental mechanisms, a stem cell- based model of early human embryogenesis is lacking. Here, we use human extended pluripotent stem cells10 to reconstitute early human development in 3-dimensions and recapitulate early embryo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Overall, our gastruloid data point to the importance of using physiologically relevant oxygen concentrations in models of embryo development. This is further corroborated by recent studies demonstrating that hypoxic culture conditions increase both the efficiency of the formation of blastocyst-like structures from human and mouse pluripotent stem cells, and ex utero culture of embryos from postimplantation to early organogenesis stages (Aguilera-Castrejon et al, 2021;Sozen et al, 2019Sozen et al, , 2021. Thus, in addition to other modulators of the microenvironment such as medium composition, and matrix, we suggest oxygen tension to be taken into consideration when modelling developmental processes in a dish, or culturing mammalian embryos ex utero.…”
Section: Discussionsupporting
confidence: 84%
“…Overall, our gastruloid data point to the importance of using physiologically relevant oxygen concentrations in models of embryo development. This is further corroborated by recent studies demonstrating that hypoxic culture conditions increase both the efficiency of the formation of blastocyst-like structures from human and mouse pluripotent stem cells, and ex utero culture of embryos from postimplantation to early organogenesis stages (Aguilera-Castrejon et al, 2021;Sozen et al, 2019Sozen et al, , 2021. Thus, in addition to other modulators of the microenvironment such as medium composition, and matrix, we suggest oxygen tension to be taken into consideration when modelling developmental processes in a dish, or culturing mammalian embryos ex utero.…”
Section: Discussionsupporting
confidence: 84%
“…Human blastoids are reassembled by aggregating a mixed population of incompletely defined stem cells (with epiblast, trophectoderm, or hypoblast-like signatures) reprogrammed from human fibroblast cells, which not only display morphologically comparable features as blastulas but also can attach to the tissue culture plates and develop into E10-like embryos with the lumenogenesis of proamniotic sac-like structure [28] (Box 1). Naïve pluripotent stem cells or hEPSCs can be also used in the construction of blastoids because of their potent differentiation capacity [29][30][31][32] (Box 4). Even though both blastoids stop their development at the E10-like stage, the significant events during this stage, especially the implantation, could be sufficiently elucidated.…”
Section: Trends In Cell Biologymentioning
confidence: 99%
“…Mouse integrated blastoids have been constructed by the aggregation of mouse expanded potential stem cells, and they can induce decidualization of the endometrium and further implant into the uterus, although they exhibit limited developmental capacity and disorganize structures at the putative gastrulation stage [36]. A similar method has been applied recently to establish human blastoids by hESPCs, iPSCs, or naïve ESCs, which are morphologically and transcriptomically akin to natural blastulas and can develop into an E10-like stage [29,31,32] (Box 1).…”
Section: Open Accessmentioning
confidence: 99%
“…A series of very recent studies with hPSCs (induced or otherwise) demonstrated that also human blastocyst-like structures (hBlastoids) can be successfully obtained by either mixing hESCs with SCs from extra-embryonic lineages or via employing naïve hEPSCs, akin to the mouse model ( Liu et al, 2021 ; Yu et al, 2021 ; Sozen et al, 2021 ; Fan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%